Real Effects of Working Capital Shocks : Theory and Evidence from Micro Data - Mahmoudzadeh, Amineh; Nili, Masoud; Nili, Farhad (Elsevier, 2018)
Our study investigates the real consequences of variations in the first and second moments of working capital requirement (WCR) in the presence of financial frictions. We introduce a theoretical link from imperfect information about WCR to firms’ performance. Firms choose non-prepaid factors of production with uncertainty about required prepayments, where their access to credit is constrained by collateral. After realization, firms with higher WCR may face financial constraints. This uncertainty influences their demand for inputs, albeit risk-neutrality. Unable to employ the projected level of prepaid input, constrained firms encounter capacity underutilization, leading to misallocation of factors. Aggregate productivity and output, will thus be deteriorated during credit contraction due to higher inefficiency. Empirical assessment of our findings, using the “Annual Survey of Iranian Manufacturing Enterprises,” shows that higher requirement for working capital tightens firms’ hired prepaid inputs, production, and capacity utilization. Furthermore, firms with more uncertain working capital will choose a lower level of production. These results are especially scaled up, when firms face financial constraints.